"Health is the Ability to Manage Yourself Without Help": How Older African American Men Define Health and Successful Aging. (21st June 2017) - Griffith, Derek M; Cornish, Emily K; Bergner, Erin M; Bruce, Marino A; Beech, Bettina M
Abstract: Objective: Few studies have explored how older African American men understand the relationship between health and successful aging. The goal of this study was to examine how older African American men's conceptions and definitions of health and notions of successful aging are interrelated. Method: Using data from 22 semistructured individual interviews with African American men ages 55–76, we examine how cultural and normative ideals about health map onto the core components of Rowe and Kahn's (1997) definition of successful aging. We also explore how these notions influence factors that have implications for health. Results: Consistent with prior research, we found that older African American men operationalized notions of health in ways that mapped onto three elements of successful aging: (a) the absence of disease and disability, (b) the ability to maintain physical and cognitive functioning, and (c) meaningful social engagement in life. A fourth theme, what men actually do, emerged to highlight how regular health practices were key components of how men define health. Conclusions: These findings highlight key elements of how older African American men conceptualize health in ways that are interrelated with yet expand notions of successful aging in ways that are critical for health promotion research and interventions.